Improved education in musculoskeletal conditions is necessary for all doctors - Åkesson Kristina; Dreinhöfer Karsten E.; Woolf A.D (The World Health Organization, 2003)
It is likely that everyone will, at some time, suffer from a problem related to the musculoskeletal system, ranging from a very common problem such as osteoarthritis or back pain to severely disabling limb trauma or rheumatoid arthritis. Many musculoskeletal problems are chronic conditions. The most common symptoms are pain and disability, with an impact not only on individuals? quality of life but also, importantly, on people?s ability to earn a living and be independent. It has been estimated that one in four consultations in primary care is caused by problems of the musculoskeletal system and that these conditions may account for up to 60% of all disability pensions. In contrast, teaching at undergraduate and graduate levels - and the resulting competence and confidence of many doctors - do not reflect the impact of these conditions on individuals and society. Many medical students do not have any clinical training in assessing patients with bone and joint problems. Under the umbrella of the Bone and Joint Decade 2000-2010, experts from all parts of the world with an interest in teaching have developed recommendations for an undergraduate curriculum to improve the teaching of musculoskeletal conditions in medical schools. The goal for each medical school should be a course in musculoskeletal medicine concentrating on clinical assessment, common outpatient musculoskeletal problems and recognition of emergencies. Improving competency in the management of musculoskeletal problems within primary care settings through improved education is the next aim, but there are needs for improvement for all professionals and at all levels within the health care system.